Perbandingan Kinerja Keuangan Industri Manufaktur Rokok Yang Go Public Di BEI Sebelum Dan Sesudah Fatwa MUI - ZUHRI, M SAIFUDIN, Zulfa Irawati, S.E., M.Si (2017)
The purpose of this research is to know the comparative financial performance on manufacturing cigarettes that go public both before and after the MUI's smoking ban. The population in this research is the financial report on cigarette manufacturing company go public listed on the Indonesia stock exchange in the form of reports on the balance sheet and profit/loss report. The sample used is a financial report that includes the balance sheets and profit/loss before the MUI on the smoking ban in 2007-2009 and after the MUI 2011-2013 year in which the MUI issued in 2010. Data obtained from the cigarette manufacturing company financial reports listed on the Indonesia stock exchange in 2007-2009 and in 2011-2013. Methods of data analysis used in this study is testing the average difference (t test). The results of descriptive per ratio showed that the average value of the Current Ratio, Quick Ratio, Cash Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Total Asset Turn Over, and Return on Equity for three years before the MUI issued better than three years after a report issued the MUI but the average value of Fixed Asset Turn Over and Return On Assets for three years before the MUI issued no better than three years after a report issued the MUI. While the result of t-test show that the financial performance of the company's cigarettes on liquidity ratio before the fatwa of smoking ban is better and different than the financial performance after the fatwa of the smoking ban but the financial performance of the company's cagarettes on solvency ratio, activity, and profitability before the fatwa prohibition of smoking is not better and not different than the financial performance after the fatwa of the smoking ban. The company is expected to further optimize its performance especially from the average value of Fixed Assets Turnover and Return On Assets, so with the optimization of the existing performance will further improve the company's performance.